The Role of Islamic Banks’ Profitability on Indonesia’s Economic Growth: A CAMELS and Endogenous Growth Model Analysis - Heri Nugraha; Eka Setiajatnika; Muhamad Ardi Nupi Hasyim; Franklin Kharisma Genta (Journal of Islamic Economics and Business, 2026)
This study examines the role of Islamic banking profitability in Indonesia’s economic growth using the CAMELS framework and an endogenous growth perspective. The analysis focuses on profitability as the main mechanism linking Islamic banking performance to real sector development during the COVID-19 pandemic and the subsequent economic recovery period. The study uses annual data from 2020 to 2023 obtained from the Financial Services Authority, Bank Indonesia, Statistics Indonesia, and the World Bank. The analytical methods include descriptive statistics, correlation and stationarity tests, and regression estimation using Ordinary Least Squares (OLS) and the System Generalized Method of Moments (GMM) to address potential endogeneity. The empirical results show that Islamic banking profitability, particularly Return on Equity (ROE), has a positive and statistically significant effect on Indonesia’s economic growth. Return on Assets (ROA) also exhibits a positive relationship with growth, although with weaker statistical significance. Other CAMELS indicators, including capital adequacy, asset quality, efficiency, and liquidity, do not have a significant direct impact on economic growth but serve as stabilizing factors for the banking system. Inflation has a negative and significant effect on economic growth, while investment shows a positive but statistically insignificant relationship. Overall, the findings confirm that profitability is the primary channel through which Islamic banking contributes to national economic growth. This study positions profitability as an explanatory variable rather than merely a performance indicator and reinforces the relevance of endogenous growth theory in the context of Islamic banking in Indonesia. Policy implications emphasize the importance of strengthening Islamic banking profitability to enhance its contribution to sustainable economic growth.